(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
After the conquest of Georgia by Russia, the culture of Georgia took a new path, it was influenced not only by the imperialist policy of Russia, but also completely changed its character and purposefulness. The empire tried to turn this sphere into a weapon of conquest, zealously attacked those basic mental problems that would weaken the basis of the identity of the Georgian nation. Georgian schools and cultural institutions acquired the function that was the main goal conqueror: assimilation of the nation, destruction of ethnocultural and ethnohistorical traditions. These processes, as in other regions of Georgia, were actively carried out in Kakheti. Therefore, the study of the education and culture of the Kakheti region in the era of tsarism is one of the serious parts of this big problem.